Exploring satisfaction, motivation and challenges of volunteering among university students - Mohamad Shukri Abdul Hamid,; Nur Shahreen Fareesha Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Students have an important role in the nation development. Active involvement in volunteer activities indirectly help the student to develop their own potential while building a better society. The main objectives of this study are threefold. Firstly, it seeks to ascertain the primary motivations driving students to engage in volunteer work, as well as the factors that discourage them from participating in such activities. Secondly, the study aims to explore the relationship between various satisfaction factors and the overall level of satisfaction experienced by students when they take part in volunteering endeavours. Lastly, the research endeavours to determine if there are significant differences in the challenges faced by students participating in volunteering, based on their gender and ethnic backgrounds. By addressing these objectives, the study intends to provide valuable insights into the motivations, satisfaction levels, and challenges associated with student involvement in volunteer work across diverse demographics. A total of 270 students from School of Quantitative Sciences (SQS), UUM were the main respondents in this research. The respondents were selected using stratified sampling. Descriptive statistics, t-test, analysis of variance (ANOVA) and regression were conducted to analyse the data. This study found that majority of the students had experienced involve in volunteerism. Respondent indicates that the item in understanding and social dimension most likely to motivate them to volunteer. Furthermore, the factors that significantly contribute to the overall volunteer satisfaction are smooth activities, benefits and cooperation from all parties. Meanwhile, basic facilities, financial provision and activities are found not significant.